2016
DOI: 10.1186/s41016-016-0023-x
|View full text |Cite
|
Sign up to set email alerts
|

Drug treatment of cerebral vasospasm after subarachnoid hemorrhage following aneurysms

Abstract: Cerebral vasospasm (CVS) is a common and severe complication of aneurysmal subarachnoid hemorrhage (aSAH). Despite the improvement in treatment of aSAH, CVS complicating aSAH has remained the main cause of death. CVS begins most often on the third day after the ictal event and reaches the maximum on the 5th-7th postictal days. Several therapeutic modalities have been employed to prevent or reverse CVS. The aim of this review is to summate all the available drug treatment modalities for vasospasm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 71 publications
(77 reference statements)
0
36
0
1
Order By: Relevance
“…Oral Nimodipine lowers the incidence of vasospasm-caused brain ischemia by 34% and the rate of ASAH poor outcomes by 40% 6 . Its neuroprotectivefeatures most likely contribute to positive results in CVS 6,14 . Nimodipinehas a low complication rate, can diminish the risk of secondary DCI and may achieve positive angiographic and clinical results 14 .…”
Section: Prevention Of Cerebral Vasospasm After Aneurysmal Subarachnomentioning
confidence: 99%
See 4 more Smart Citations
“…Oral Nimodipine lowers the incidence of vasospasm-caused brain ischemia by 34% and the rate of ASAH poor outcomes by 40% 6 . Its neuroprotectivefeatures most likely contribute to positive results in CVS 6,14 . Nimodipinehas a low complication rate, can diminish the risk of secondary DCI and may achieve positive angiographic and clinical results 14 .…”
Section: Prevention Of Cerebral Vasospasm After Aneurysmal Subarachnomentioning
confidence: 99%
“…Statins are here reviewed as another group of potential vasospasm preventing drugs. Some trials suggested that they boost cerebral vascular reactivity 6,14 .One meta-analysis showed beneficial effects of statins on incidence of delayed vasospasm, ischemic injury, and mortality, while another meta-analysis failed to show such results 16 . Recent meta-analysis showed higher number of complications with statin therapies than their favorable outcomes 17 .…”
Section: Prevention Of Cerebral Vasospasm After Aneurysmal Subarachnomentioning
confidence: 99%
See 3 more Smart Citations